Human Resources Management Innovation - Kossek, Ellen Ernst (Human Resource Management, 1987)
AbstractGuided by a general manager's perspective of human resources management (HRM), this paper identifies key factor affecting the introduction of HRM innovations in organizations. Because the essence of market and technological leadership is the development of the organizational capacity to carry out inventive ideas, it is critical to understand the main forces influencing HRM innovation. Following a definition of HRM innovation, six propositions are discussed using current and historical examples. Since HRM innovation also involves change in the social system of the organization, the adoption and diffusion of these innovations can be attributed not only to external environmental forces but also to social processes.